2019
DOI: 10.1001/jamafacial.2019.0937
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Opioid Prescribing Habits for Patients Undergoing Rhinoplasty and Septoplasty

Abstract: IMPORTANCEOpioid prescriptions have increased substantially over the last 2 decades, contributing to the opioid epidemic. Physician practices and legislative changes play a key role in decreasing prescription opioid use.OBJECTIVE To evaluate changes in opioid prescribing habits for patients undergoing rhinoplasty and/or septoplasty before and after the adoption of new opioid legislation. DESIGN, SETTING, AND PARTICIPANTSThis single-institution case-control study examined opioid prescribing habits for 80 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Patient and public health outcomes, evaluated in less than half of the studies, included changes in patient-reported pain scores or quality of life, 18,19 unplanned access to additional medical care for pain or related issues, [20][21][22][23][24][25] concomitant opioid and benzodiazepine prescribing, [26][27][28][29][30] prescription opioid or heroin overdose hospitalizations or trends, 26,31,32 transition from acute to prolonged use after surgical procedures, 18,[33][34][35][36][37] allcause mortality, 18 patient retention rate, 28 and changes in number of prescribers or pharmacies. 26,31,38 One study also evaluated prescriber utilization of an electronic medical record (EMR) alert tool designed to facilitate compliance with OA prescribing limits.…”
Section: Resultsmentioning
confidence: 99%
“…Patient and public health outcomes, evaluated in less than half of the studies, included changes in patient-reported pain scores or quality of life, 18,19 unplanned access to additional medical care for pain or related issues, [20][21][22][23][24][25] concomitant opioid and benzodiazepine prescribing, [26][27][28][29][30] prescription opioid or heroin overdose hospitalizations or trends, 26,31,32 transition from acute to prolonged use after surgical procedures, 18,[33][34][35][36][37] allcause mortality, 18 patient retention rate, 28 and changes in number of prescribers or pharmacies. 26,31,38 One study also evaluated prescriber utilization of an electronic medical record (EMR) alert tool designed to facilitate compliance with OA prescribing limits.…”
Section: Resultsmentioning
confidence: 99%
“…11,21 Our results also confirm previous literature which states that a reduction of opioids still guarantees satisfactory pain control and does not lead to increased second prescriptions. 22…”
Section: Discussionmentioning
confidence: 99%
“…After a review of the available literature on opioid requirements after ORL surgery, a protocol was created for maximum postoperative opioid prescriptions based on anatomic site of surgery 6–36 . Of note, it was decided that pediatric patients should not receive opioid prescriptions regardless of surgical site, given the higher risk of adverse events in this patient population related to variability in opioid metabolism and risks of respiratory depression, possibly leading to death 37 .…”
Section: Methodsmentioning
confidence: 99%